Audit pricing puzzle: Do audit firm industry specialization and audit report lag matter? - Ebenezer Nana Yeboah; Bismark Addai; Kingsley Opoku Appiah (Cogent Business & Management, 2023)
This study examines whether audit firm industry specialization and audit report time lag (ARL) matter in the audit fees puzzle. Specifically, we examine the moderating effect of audit time lag on the audit firm industry specialization and audit fees nexus. We use dataset from 100 quoted and unquoted Ghanaian firms from 2008 to 2018. We find that audit firm industry specialization exhibits a significant positive impact on audit fees and a significant negative effect on ARL. The results of the interaction between audit firm industry specialization and ARL also display a negative association with audit fee, signifying that specialization significantly reduces audit fee premium paid provided these experts produce the financial report in a short time. Further analysis on large and small companies, state-owned and private companies, weak and strong internal controls also indicate the significance of audit firm industry specialization and reporting time lag in explaining audit pricing puzzle. The novelty aspect of this study is the analysis of the moderation effect of audit timeliness on the audit firm industry specialization and audit fees nexus in the context of a lax enforcement of Generally Accepted Accounting Principles environment.
Keywords: 650; audit fees; audit market concentration; audit report time lag; industry experience; industry knowledge